2019
DOI: 10.2169/internalmedicine.1969-18
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Pulmonary Arteriovenous Malformation with Non-tuberculous Mycobacteria Infection Caused by Perfusion from the Pulmonary Artery and Bronchial Artery after Coil Embolization

Abstract: Recurrence of an embolized pulmonary arteriovenous malformation (PAVM) is common after coil embolization. A 23-year-old woman who had undergone multiple instances of transcatheter coil embolization was admitted with hypoxia and hemoptysis. A PAVM in the left S6 was found to be recanalized by reperfusion through the pulmonary and bronchial arteries. The left S6 was partially resected; the specimen contained necrotic granulomas and non-tuberculous mycobacteria (NTM) around the PAVM. Clinicians should consider po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The embolic material appeared to act as a foreign material and prevented healing of the infection, resulting in chronic inflammation around the coils. In addition, it was reported that the presence of non-tuberculous mycobacteria was confirmed by examinations after lobectomy performed for hemoptysis after coil embolization of a PAVM [6] . In contrast, the present article is the first to describe histopathological results including chronic inflammation, and bronchial epithelium extension into the sac of the PAVM.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The embolic material appeared to act as a foreign material and prevented healing of the infection, resulting in chronic inflammation around the coils. In addition, it was reported that the presence of non-tuberculous mycobacteria was confirmed by examinations after lobectomy performed for hemoptysis after coil embolization of a PAVM [6] . In contrast, the present article is the first to describe histopathological results including chronic inflammation, and bronchial epithelium extension into the sac of the PAVM.…”
Section: Discussionmentioning
confidence: 95%
“…To clarify causes of hemoptysis, we reviewed articles extracted from PubMed using search terms “pulmonary arteriovenous malformations” and “embolization” and “hemoptysis.” Four cases of hemoptysis after embolization for PAVMs were identified [5] , [6] , [7] , [8] . In total, 6 cases including those 4 cases, and our 2 cases are summarized in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation